Prenatal Stress Alters Progestogens to Mediate Susceptibility to Sex-Typical, Stress-Sensitive Disorders, such as Drug Abuse: A Review - Frye, Cheryl A.; Paris, Jason J.; Osborne, Danielle; Campbell, Joanna; Kippin, Tod (Frontiers in Psychiatry, 2011)
Maternal–offspring interactions begin prior to birth. Experiences of the mother during gestation play a powerful role in determining the developmental programming of the central nervous system. In particular, stress during gestation alters developmental programming of the offspring resulting in susceptibility to sex-typical and stress-sensitive neurodevelopmental, neuropsychiatric, and neurodegenerative disorders. However, neither these effects, nor the underlying mechanisms, are well understood. Our hypothesis is that allopregnanolone, during gestation, plays a particularly vital role in mitigating effects of stress on the developing fetus and may mediate, in part, alterations apparent throughout the lifespan. Specifically, altered balance between glucocorticoids and progestogens during critical periods of development (stemming from psychological, immunological, and/or endocrinological stressors during gestation) may permanently influence behavior, brain morphology, and/or neuroendocrine-sensitive processes. 5α-reduced progestogens are integral in the developmental programming of sex-typical, stress-sensitive, and/or disorder-relevant phenotypes. Prenatal stress (PNS) may alter these responses and dysregulate allopregnanolone and its normative effects on stress axis function. As an example of a neurodevelopmental, neuropsychiatric, and/or neurodegenerative process, this review focuses on responsiveness to drugs of abuse, which is sensitive to PNS and progestogen milieu. This review explores the notion that allopregnanolone may effect, or be influenced by, PNS, with consequences for neurodevelopmental-, neuropsychiatric-, and/or neurodegenerative- relevant processes, such as addiction.